Eksplorasi Desain Dengan Peta Morfologi (Studi Kasus: Perancangan Desain Mebel Terinspirasi Gaya Memphis Era 1980an) - Devanny Gumulya (Jurnal PATRA, 2022)
The paper studies how morphological charts from engineering methods are applied in a creative design process. The method allows designers to think differently and logically. Morphological chart offers vast possibilities for design exploration that can be useful in educating nascent designers. On the other hand, history have inspired many designers to create many new things. Memphis is postmodern design style that occurred between 1981-1987, characterized by form following fun paradigm by creating objects that are bizarre from common object over time. This is a paper analyzing student design history projects to create a design inspired by Memphis design. It presents the framework for exploring design with morphological charts. The chart generating five new ideas ranging from very to less similar to Memphis-like style. Using the morphological chart method, the study discovered three key factors affecting the difference of ideas generated on the study: level of variation, which deals with how many variations the means can provide, the more variations the newer ideas can be generated. Unity level means showing how each element is in harmony with each other. Level of abstraction means the degree of inspiration from the original idea. By paying attention to these three factors, morphological chart can produce better design.